First trimester HtrA1 maternal plasma level and spontaneous preterm birth. (16th February 2022) - Giannubilo, Stefano Raffaele; Licini, Caterina; Picchiassi, Elena; Tarquini, Federica; Coata, Giuliana; Fantone, Sonia; Tossetta, Giovanni; Ciavattini, Andrea; Castellucci, Mario; Giardina, Irene; Gesuita, Rosaria; Marzioni, Daniela
Abstract: Objectives: High temperature requirement A1 (HtrA1) is a serine protease detected in maternal plasma and in placental tissues during normal gestation and in various pathological conditions. The purpose of this study was to determine whether the maternal plasma concentration of HtrA1 in first trimester, alone or combined with other maternal factors, can be used to identify women at risk for spontaneous preterm birth (SPTB). Study design: This is a cohort study on pregnant women at 12 weeks of gestation recruited between 2014 and 2016 and prospectively followed until delivery. One hundred and fifty-nine women were included in the study: 140 women delivered at term and 19 (11.9%) delivered spontaneously preterm. Plasma samples were assessed for HtrA1 by ELISA and data were compared between women which delivered at term with women which delivered preterm. A multiple logistic regression analysis was used to estimate the independent effect of women's characteristics on the probability of a SPTB. Results: SPTB was significantly associated with log HtrA1 values at 12 weeks of gestation, BMI before pregnancy and physical activity. In particular, the probability of a SPTB increases of 79% for every added unit of log HtrA1, while decreases of 18% for every added unit of BMI. In addition, physical activity was found as an important protective factor. The ROC curve showed that the model had a good accuracy in predicting SPTB, with an AUC equal to 0.83 (95%CI: 0.73–0.91). Conclusions: Maternal plasma HtrA1 may be considered a marker of SPTB. In addition, our model indicates two factors that could be modified to reduce the risk of SPTB, i.e. BMI before pregnancy and maternal physical activity.